Spider-man 3 - Raimi, Sam; Ziskin, Laura; Arad, Avi; Curtis, Grant (Culver City, Calif. : Sony Pictures Home Entertainment, 2007)
Peter Parker's adventures as Spider-man continue as he struggles with an alien form that turns his suit black and releases his inner demons, and faces villains Sandman, Venom, and the New Goblin
Title from title screen
Sequel to the 2002 movie'Spider-man'
Features: filmmaker and cast commentaries, bloopers, Snow Patrol music video, photo galleries
Director of photography, Bill Pope ; film editor, Bob Murawski ; music by, Christopher Young ; costume designer, James Acheson ; production designers, J. Michael Riva, Neil Spisak
Casts: Tobey Maguire, Kirsten Dunst, James Franco, Topher Grace, Thomas Haden Church
In English with optional English or Indonesian subtitles
Keywords: Spider-Man (Fictitious character) -- Drama; Personality change -- Drama; Good and evil -- Drama; Man-woman relationships -- Drama; Superhero films